Empirical Analysis of the Labor Market from the Monetary Policy Perspective - Ruschka, Adam; Chytilová, Helena; Bartůsková, Lucia; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis investigates the labor market as a primary driver of domestic inflationary pressures, with the overarching goal of enhancing the understanding of the labor market and informing central bank strategies to achieve price stability. First, the thesis examines the interconnection between labor income shocks and economic activity. Using a dynamic panel System GMM analysis on data from 27 European countries (from 1998 to 2024) alongside a unique firm-level dataset from the Czech Republic (from 2010 to 2024), the thesis demonstrates that negative labor income shocks exert a smaller-than-expected influence on household consumption, maintaining inflationary pressures, that monetary policy can mitigate. Second, the Phillips curve framework is tested by SVAR model and regression decomposition for validity and used in conjunction with an innovative multivariate Kalman filter setup to derive new NAIRU and NAIRU gap estimates for 28 European countries spanning from 2000 to 2024. The results show tight and synchronized European labor markets. The application of Okun’s law estimations in the Czech Republic further illustrates the practical utility of these measures for both academic inquiry and policy formulation. Third, by leveraging high-frequency online job advertisement data to develop entirely new wage statistics and introducing the Labor Utilization Composite Index (LUCI) derived through a novel empirical methodology using VAR model, Kalman filter and dynamic principal component analysis, the thesis offers advanced tools for real-time labor market assessment. These tools significantly enhance the monetary policy-making process by providing more timely and accurate indicators of labor market conditions. The contributions of this thesis advance theoretical understanding of labor market dynamics and furnish practical instruments for monetary policymakers to better achieve the objective of price stability.
Vedoucí práce: Helena Chytilová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomická teorie [obor disert. práce]; disertace; dissertations